Establishment and construction of the school and the church of the heart of Jesus in the town of San Bartolome de Honda (1745-1805) - Pinzón Rivera, José Alexander (Corporación Universitaria del Caribe, CECAR., 2015)
Abstract: This article aims to study from the historical and architectural point of view the historical and architectural point of view the construction process of the first venues for the school and the church of the Order of the Society of Jesus in the old town of San Bartolome de Honda. It addresses three aspects in particular, the place originally occupied by these two buildings, then transferred to a more dynamic bank of the Gualí river in 1746. In the end, the events that gave rise to the change of use of this architectural complex by the Aguardiente Factory are shown. First, from the expulsion of the religious order of the territory of Nueva Granada and then by the physical disappearance of the building due to natural causes in 1805. ___Keywords: Honda, school, church, Jesuits, colonial architecture, aguardiente factory. ___Resumen: El presente artículo tiene por objeto estudiar desde el punto de vista histórico y arquitectónico el proceso de construcción de las primeras sedes para el colegio e iglesia de la orden de la Compañía de Jesús en la antigua Villa de San Bartolomé de Honda. Se responde a tres aspectos en concreto, el lugar que ocuparon inicialmente estas dos edilicias, su posterior traslado a un espacio más dinámico a orillas del río Gualí en 1746. Al final, se presentan los sucesos que dieron pie al cambio de uso de este complejo arquitectónico por Fábrica de Aguardientes; primero a partir de la expulsión de la orden religiosa del territorio de la Nueva Granada y luego por la desaparición física de la edificación por causas naturales en 1805. ___Palabras clave: Honda, colegio, iglesia, jesuitas, arquitectura colonial, fabrica de aguardientes. ___Recibido: 06 de septiembre de 2015. Aceptado: 28 de octubre de 2015.